Studi Tentang Teori GONE dan Pengaruhnya Terhadap Fraud Dengan Idealisme Pimpinan Sebagai Variabel Moderasi: Studi Pada Pengadaan Barang/Jasa di Pemerintahan - Isgiyata, Jaka; indayani, indayani; Budiyoni, Eko (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This study aims to examine the effect of GONE theorys variables on the procurement fraud of government goods/services by using variables of leadership idealism as a moderating variable. This study uses question instruments for each variable: Greed, Opportunity, Need, and Exposes from Bologne (1993), Leadership Idealism from Tappen (1994) and Procurement Fraud of Government Goods/Services. This study collects primary data gathered from the respondents perception in Kebumen District Government agencies. The analysis technique used is Moderated Regression Analysis (MRA). The results of this study demonstrate that the existence of Exposes (low penalty level) and lack of leadership idealism will increase the potential procurement fraud of goods/services in government. In other words without the punishment that can provide a deterrent effect and less idealistic leadership will be more and more potential individuals within the bureaucracy associated in the procurement process of goods/services to conduct fraud.